Membranes for CO2 /CH4 and CO2/N2 Gas Separation. Issue 2 (21st November 2019) - Chawla, Muhammad; Saulat, Hammad; Masood Khan, Muhammad; Mahmood Khan, Muhammad; Rafiq, Sikander; Cheng, Linjuan; Iqbal, Tanveer; Rasheed, M. Imran; Farooq, Muhammad Zohaib; Saeed, Muhammad; Ahmad, Nasir M.; Khan Niazi, Muhammad Bilal; et al.
Abstract: Membrane technology has emerged as a leading tool worldwide for effective CO2 separation because of its well‐known advantages, including high surface area, compact design, ease of maintenance, environmentally friendly nature, and cost‐effectiveness. Polymeric and inorganic membranes are generally utilized for the separation of gas mixtures. The mixed‐matrix membrane (MMM) utilizes the advantages of both polymeric and inorganic membranes to surpass the trade‐off limits. The high permeability and selectivity of MMMs by incorporating different types of fillers exhibit the best performance for CO2 separation from natural gas and other flue gases. The recent progress made in the field of MMMs having different types of fillers is emphasized. Specifically, CO2 /CH4 and CO2 /N2 separation from various types of MMMs are comprehensively reviewed that are closely relevant to natural gas purification and compositional flue gas treatment Abstract : Membrane‐based techniques emerged as the most effective option for the separation and/or capture of CO2 . Different types of membranes are reviewed with the main emphasis placed on mixed‐matrix membranes with various types of fillers. Such membranes combine the advantages of both polymeric and inorganic membranes and exhibit the best performance for CO2 separation from natural gas and other flue gases.